Liquid ventilation with perflubron in the treatment of rats with pneumococcal pneumonia. - Dickson, E; Heard, S; Tarara, T; Weers, J; Brueggemann, A; Doern, G (2002)
OBJECTIVE: To determine the efficacy of liquid ventilation using a medical-grade perfluorocarbon (perflubron) combined with parenteral or intratracheal antibiotics in a rat model of pneumonia. DESIGN: Prospective, laboratory investigation. SETTING: Experimental laboratory in a university medical center. SUBJECTS: Wistar rats (n = 112). INTERVENTIONS: One day after intratracheal inoculation with Streptococcus pneumoniae, rats received one of five experimental treatments or no treatment (control): modified liquid ventilation (MLV), intramuscular ampicillin, MLV plus intramuscular ampicillin, MLV with intratracheal ampicillin, or MLV plus ampicillin PulmoSpheres. MEASUREMENTS AND MAIN RESULTS: Animals receiving MLV plus intramuscular ampicillin, MLV with intratracheal ampicillin, or MLV plus ampicillin PulmoSpheres had significantly improved 10-day survival rates (85%, 72%, and 72%, respectively) compared with all other groups (0% to 25%). CONCLUSIONS: MLV in combination with either intramuscular, intratracheal, or PulmoSpheres ampicillin improved survival as compared with MLV alone or the same dose of antibiotics delivered intramuscularly.